2019
DOI: 10.3390/ijerph16020202
|View full text |Cite
|
Sign up to set email alerts
|

Is Childhood Overweight/Obesity Perceived as a Health Problem by Mothers of Preschool Aged Children in Bangladesh? A Community Level Cross-Sectional Study

Abstract: Childhood obesity is rapidly rising in many developing countries such as Bangladesh; however, the factors responsible for this increase are not well understood. Being the primary caregivers of children, particularly in developing countries, maternal perceptions and knowledge could be important factors influencing the weight status of children. This study aimed to assess maternal perceptions of childhood obesity and associated socio-demographic factors in Bangladesh. A cross-sectional study using stratified ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…In this study, the mothers who had high school education and above and the mothers who had normal weight according to body mass index perceived their children's weight more accurately, and there was a significant difference between mother 's educational status, mother' s body mass index and mother 's perception of her child' s weight. Similar to our research findings, Hossain et al (2019) expressed that mothers perceived the child's weight more accurately as their educational status increased (20). It is seen that the education level of the mothers is important for their children to perceive their weight correctly.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, the mothers who had high school education and above and the mothers who had normal weight according to body mass index perceived their children's weight more accurately, and there was a significant difference between mother 's educational status, mother' s body mass index and mother 's perception of her child' s weight. Similar to our research findings, Hossain et al (2019) expressed that mothers perceived the child's weight more accurately as their educational status increased (20). It is seen that the education level of the mothers is important for their children to perceive their weight correctly.…”
Section: Discussionsupporting
confidence: 88%
“…In the study of Carrillo-Larco (2017), the overlap between the mothers' perceptions and the actual weight of the child was very low and that the chubby child was considered as a healthy child (1). Hossain et al (2019) asserted that more than twothirds of mothers were not aware that obesity was a health problem in childhood (20). Lindsay et al (2010) found that the majority of mothers were of the opinion that having a chubby child meant being a good parent which was due to familial and cultural influence, and that some of the mothers perceived their children as skinny even if they had normal weight (13).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, ethnic comparisons were not available for any of the other studies; although ethnic differences regarding both risk for and prevalence of obesity are well known (Haslam et al 2006). There is the notion that parents in developing countries prefer children with a higher BMI, likely due to cultural and historical influences where families would have struggled to provide food for several hungry mouths (Hossain et al 2019). Lutchmansingh et al studied body image perception in 11-16 year old Trinidadian children and found that boys perceived their body image in agreement with their BMI classification, whereas girls tended to view their body image as heavier than their actual BMI classification (Lutchmansingh et al 2014).…”
Section: Results Of Secular Trends Analysismentioning
confidence: 99%
“…preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted November 18, 2020. ; https://doi.org/10.1101/2020.11.16.20232421 doi: medRxiv preprint the variance. In contrast, mothers tend to consider a relatively high child weight as an indicator of good health, especially in China [52][53][54]. They thus may be less concerned about child overweight than mothers in other countries.…”
Section: Discussionmentioning
confidence: 98%